Placental lncRNA expression associated with placental cadmium concentrations and birth weight. Issue 1 (10th May 2020) - Hussey, Michael R; Burt, Amber; Deyssenroth, Maya A; Jackson, Brian P; Hao, Ke; Peng, Shouneng; Chen, Jia; Marsit, Carmen J; Everson, Todd M
Abstract: Heavy metal exposures, such as cadmium, can have negative effects on infant birth weight (BW)—among other developmental outcomes—with placental dysfunction potentially playing a role in these effects. In this study, we examined how differential placental expression of long non-coding RNAs (lncRNAs) may be associated with cadmium levels in placenta and whether differences in the expression of those lncRNAs were associated with fetal growth. In the Rhode Island Child Health Study, we used data from Illumina HiSeq whole transcriptome RNA sequencing ( n  = 199) to examine association between lncRNA expression and measures of infant BW as well as placental cadmium concentrations controlled for appropriate covariates. Of the 1191 lncRNAs sequenced, 46 demonstrated associations ( q  < 0.05) with BW in models controlling for infant sex, maternal age, BMI, maternal education, and smoking during pregnancy. Furthermore, four of these transcripts were associated with placental cadmium concentrations, with MIR22HG and ERVH48-1 demonstrating increases in expression associated with increasing cadmium exposure and elevated odds of small for gestational age birth, while AC114763.2 and LINC02595 demonstrated reduced expression associated with cadmium, but elevated odds of large for gestational age birth with increasing expression. We identified relationships between lncRNA expression with both placental cadmium concentrations and BW. This study provides evidence that disrupted placental expression of lncRNAs may be a part of cadmium's mechanisms of reproductive toxicity.